Implementation of a circular bioeconomy: obtaining cellulose fibers derived from portuguese vine pruning residues for heritage conservation, oxidized with TEMPO and ultrasonic treatment - Araújo, Liliana (2023)
Inspired by the principles of the circular economy, using vineyard pruning residues as a source of raw materials for producing nanocellulose is a promising approach to transforming vineyard resources into value-added products. This study aimed to obtain and characterize cellulose and cellulose nanofibers from such sources. The cellulose collected from different fractions of micronized stems (500, 300, 150 μm, and retain) of vines was submitted to autohydrolysis and finally bleached. Soon, it underwent treatment via (2,2,6,6-tetrametil-piperidi-1-nil)oxil (TEMPO) oxidation and ultrasonic to obtain nanocellulose fibers. The cellulose films were obtained at a microscale thickness of 0.05 ± 0.00; 0.37 ± 0.03; 0.06 ± 0.01 e 0.030 ± 0.01 mm, with the following particle size: 500 µm, 300 µm, 150 µm, and retain (<150 µm). The bleaching efficiency of the cellulose fibers of each particle size fraction was evaluated for color through a colorimeter. In addition, the extraction of cellulose fibers was assessed by infrared with Fourier transform, and size and shape were assessed by microscopy. Differential scanning calorimetry and X-ray diffraction were performed to confirm the thermal and crystalline properties. Combining autohydrolysis with a bleaching step proved to be a promising and ecological alternative to obtain white fractions rich in cellulose. It was possible to perform the extraction of cellulose to obtain nanocellulose fibers from vine pruning residues for the development of coatings for the conservation of heritage buildings from environmental conditions through an environmentally friendly process.